Banking Reform in the Lower Mekong Countries - Unteroberdoerster, Olaf (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2004)
This paper reviews recent banking reform efforts in the lower Mekong countries (LMCs), comprising Cambodia, the Lao People's Democratic Republic, and Vietnam. Linked by close economic and cultural ties, the three LMCs face the dual challenge of economic development and transition to market-based economies. Two-tier banking systems were formally introduced in the late 1980s. However, state-owned banks with weak balance sheets continue to dominate the banking systems of Vietnam and Lao P.D.R. Cambodia's main challenge is to reconstruct a banking system after decades of civil strife. Based on progress made and brief cross-country comparisons, the paper identifies key challenges and options for further reform.